2016
DOI: 10.3329/jbau.v13i1.28725
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency of Boro rice production in Bangladesh: A case of bio-slurry application

Abstract: The main objective of this study is to estimate the impact of bioslurry to Boro rice production in Bangladesh. Translog production function through Stochastic Frontier Apoproach (SFA) was applied for estimating the efficiency of Boro production. Data were collected from biogas users in the four district of Bangladesh: Mymensingh, Pabna, Thakurgaon and Dinajpur. Biogas users have received significant impact from bio-slurry to Boro rice production while chemical fertilizers have no significant impact to same pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…This result, thus, is consistent with the finding of Balde, Kobayashi [20], who found that education level was significant and negatively affecting the TE of Mangrove rice production in the Guinean coastal area. Additionally, Kabir, Musharraf [25] who estimate the impact of bio-slurry to Boro rice production in Bangladesh, also found the same negative sign of coefficient of education relation to production inefficiency of rice. Besides, the variable of family size also has a negative and significant impact (on TE).…”
Section: Technical Inefficiency Model and Affecting Factorsmentioning
confidence: 63%
See 1 more Smart Citation
“…This result, thus, is consistent with the finding of Balde, Kobayashi [20], who found that education level was significant and negatively affecting the TE of Mangrove rice production in the Guinean coastal area. Additionally, Kabir, Musharraf [25] who estimate the impact of bio-slurry to Boro rice production in Bangladesh, also found the same negative sign of coefficient of education relation to production inefficiency of rice. Besides, the variable of family size also has a negative and significant impact (on TE).…”
Section: Technical Inefficiency Model and Affecting Factorsmentioning
confidence: 63%
“…Coelli [22] had developed the software FRONTIER 4.1c, which can be used to generate both the stochastic production frontier and the inefficiency model simultaneously. Moreover, the FRONTIER 4.1c was widely applied in different fields of research in the recent years, especially in agricultural studies like [15,17,20,[23][24][25][26][27][28] for instance.…”
Section: Methodsmentioning
confidence: 99%
“…However, no studies have evaluated how much of these organic fertilizers influence on yield and efficiency of rice production. Previous researches have been done on mulching and composting ( Termorshuizen et al., 2004 ; Jusoh et al., 2013 ), fertilizer management ( Srivastava et al., 2016 ), green wastage usage ( Gong et al., 2018 ; Eldridge et al., 2018 ), rice yield ( Rahman, 2003 ; Thakuria et al., 2009 ; Bäckman et al., 2011 ; Barison and Uphoff, 2011 ; Kabir et al., 2016 ). However, organic fertilizer's impact on rice production and technical efficiency is still a gap in research.…”
Section: Introductionmentioning
confidence: 99%
“…However, organic fertilizer's impact on rice production and technical efficiency is still a gap in research. Although, many studies have estimated stochastic frontier production for farms to analyze technical efficiency and contributions of different inputs ( Battese and Coelli, 1995 ; Greene, 2005 ; Bäckman et al., 2011 ; Kabir et al., 2016 ; Gautam and Ahmed, 2019 ). However, almost no one focuses on applying organic fertilizer with correction of sample selection for rice production.…”
Section: Introductionmentioning
confidence: 99%
“…Coelli [22] had developed the software FRONTIER 4.1c, which can be used to generate both the stochastic production frontier and the inefficiency model simultaneously. Moreover, the FRONTIER 4.1c was widely applied in different fields of research in the recent years, especially in agricultural studies like [15,17,20,[23][24][25][26][27][28] for instance. 1 According to 14.…”
Section: Methodsmentioning
confidence: 99%